FOXN4 affects myocardial ischemia-reperfusion injury through HIF-1α/MMP2-mediated ferroptosis of cardiomyocytes: FOXN4 regulates ferroptosis of cardiomyocytes to affect myocardial ischemia-reperfusion injury - Wang, Jiyang; Deng, Min; Yang, Jiaona; Zhou, Xiaojuan; Yang, Peng; Li, Yan; Zhang, Guimin (Cellular and Molecular Biology, 2023)
Myocardial ischemia-reperfusion injury (MIRI) is an important factor leading to myocardial injury and necrosis, and can induce ischemic heart disease. Forkhead box protein N4 (FOXN4) belongs to the gene family of Fork head domain (Fox) transcription factors and plays an important role in heart formation and function. However, whether FOXN4 is involved in MIRI progression is unknown. In this study, we investigated the clinicopathological significance and potential mechanisms of FOXN4 in MIRI. The expressions of FOXN4 and MMP2 were measured by quantitative reverse transcriptase polymerase chain reaction, apoptosis was detected by flow cytometry, and cell viability was detected by examining EdU incorporation into DNA. The signaling pathway related proteins FOXN4, MMP2, HIF-1α, apoptosis-related proteins Bcl-2 and Bax, and ferroptosis-related proteins TFR1 and IREB2 were detected by western blot, the levels of malondialdehyde (MDA), Fe2+, reactive oxygen species (ROS), and glutathione were detected by commercially available kits, and the cardiac histopathology after MIRI was evaluated by hematoxylin and eosin staining. We found that knockdown of FOXN4 alleviated oxidative stress, inhibited ROS production, and inhibited ferroptosis in MIR-injured tissues and cardiomyocytes. In addition, knockdown of FOXN4 inhibited myocardial injury, improved myocardial cell viability, restored myocardial function, and alleviated MIRI. We interrogated the mechanism and found that FOXN4 can enhance its binding to HIF-1α, up-regulate the expression of MMP2, and mediate ferroptosis to regulate the functional activity of cardiomyocytes to affect the progression of MIRI. This study provides new insights into the role of FOXN4 in MIRI progression and suggests that FOXN4 may represent a potential therapeutic target in MIRI progression by regulating the active function of cardiomyocytes through HIF-1α/MMP2-mediated ferroptosis.